Burnout Assessment Tool Development and Validation for Healthcare Workers: A Psychometric Approach Using Rasch Modelling and Exploratory Factor Analysis - Ismail, Rosnah; Vallasamy, Suriya Kumareswaran (Kesmas, 2025)
Burnout remains a significant occupational threat to healthcare workers (HCWs). Existing instruments, e.g., the Maslach Burnout Inventory, have limited applicability in healthcare-specific contexts. This study aimed to develop and validate the Burnout Scale for Assessing Stress in Healthcare Workers (BSAS-HCW), designed to measure cognitive and emotional exhaustion. A cross-sectional survey was conducted among 245 Malaysian HCWs representing diverse roles, including staff nurses (57.7%), house officers (14.3%), medical officers (13.5%), specialists (5.7%), pharmacists (4.5%), and other HCWs. Exploratory factor analysis revealed a two-factor structure with strong internal consistency (Cronbach's alpha: cognitive = 0.95; emotional = 0.97), and all items loaded above 0.4. Rasch analysis supported unidimensionality, robust item fit, and minimal differential item functioning across sex and ethnicity. Person and item reliability exceeded 0.93, with Wright Maps indicating effective item-person targeting. The instrument explained over 70% of the total variance, demonstrating strong psychometric validity. The BSAS-HCW provided a culturally and occupationally relevant tool for assessing burnout among HCWs in high-stress clinical environments. Its dual-domain design addresses the cognitive and emotional toll of burnout more comprehensively than existing tools, enabling more effective detection, monitoring, and intervention strategies across diverse healthcare roles.